High Density Lipoproteins From Biological Understanding to Clinical Exploitation - von Eckardstein, Arnold; Kardassis, Dimitris (Handbook of Experimental Pharmacology, 2015)
In this Handbook of Experimental Pharmacology on "High Density Lipoproteins - from biological understanding to clinical exploitation" contributing authors (members of COST Action BM0904/HDLnet) summarize in more than 20 chapters our current knowledge on the structure, function, metabolism and regulation of HDL in health and several diseases as well as the status of past and ongoing attempts of therapeutic exploitation. The book is of interest to researchers in academia and industry focusing on lipoprotein metabolism, cardiovascular diseases and immunology as well as clinical pharmacologists, cardiologists, diabetologists, nephrologists and other clinicians interested in metabolic or inflammatory diseases.